Real World Experience of Crizotinib in 104 Patients With ALK Rearrangement Non-small-cell Lung Cancer in a Single Chinese Cancer Center - Liu, Chang; Yu, Hui; Long, Qianqian; Chen, Haiquan; Li, Yuan; Zhao, Weixin; Zhao, Kuaile; Zhu, Zhengfei; Sun, Si; Fan, Min; Chang, Jianhua; Wang, Jialei (Frontiers in Oncology, 2019)
Purpose: Our study aimed to provide data on effectiveness, safety of crizotinib treatment, brain metastases, progression patterns and sequential therapy beyond crizotinib treatment in patients with advanced ALK-positive NSCLC in China. Methods: We reviewed the medical records of crizotinib-treated NSCLC patients with ALK-rearrangement between May 2014 and May 2018 at Fudan University Shanghai Cancer Center. All patients received crizotinib with 250 mg twice daily. Main outcome measures were progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR), the second PFS (PFS2), overall survival (OS), and adverse events. Results: One hundred and four patients with ALK-positive NSCLC were included in this retrospective study. ORR and DCR were 82.7% and 98.1%, respectively. The estimated PFS and OS were 13.0 months (95% CI 9.0-17.0 months) and 36.0 months (95%CI 31.0-41.0 months), respectively. Multivariable analysis showed that young age, presence of baseline adrenal gland metastases and non-adenocarcinoma were independent predictive factors for poorer PFS. Presence of baseline adrenal gland metastases, non-adenocarcinoma, intrathoracic progression and shorter crizotinib treatment time were associated with worse OS. Patients without baseline brain metastases (BBM) who were administered with crizotinib as first-line therapy can achieve a significantly longer PFS than those who received crizotinib as second or later line therapy (p=0.006). For patients with BBM receiving sequential therapy beyond the first disease progression after crizotinib treatment (1st PD), crizotinib beyond progressive disease (CBPD) plus local therapy can lead to a significantly longer PFS2 (67.0 weeks vs 21.0 weeks; p=0.046). Additionally, the OS was significantly longer in patients achieving 1st PD who received CBPD plus local therapy than those who did not receive CBPD or local therapy (35.0 months vs 24.0 months, p=0.041). Presence of brain metastases at any time was in association with worse PFS. No unexpected adverse effects were reported. Conclusions: Crizotinib was effective and well tolerated in Chinese patients with ALK-positive, advanced NSCLC in real-world clinical practice. For patients without BBM, crizotinib as first-line therapy can lead to a longer PFS than second-or later line therapy. CBPD plus local therapy after 1st PD beyond crizotinib is feasible and effective in clinical routine practice.